The Twilight of the Avant-Garde - Mayhew, Jonathan (Contemporary Hispanic and Lusophone Cultures, 2009)
Twilight of the Avant-Garde: Spanish Poetry 1980-2000 addresses the central problem of contemporary Spanish poetry: the attempt to preserve the scope and ambitiousness of modernist poetry at the end of the twentieth century. Jonathan Mayhew first offers a critical analysis of the called 'poetry of experience' of Luis García Montero, a tendency that is based on the supposed obsolescence of the modernist poetics of the first half of the century. While the 'poetry of experience' presents itself as a progressive attempt to 'normalise' poetry, to make it accessible to the common reader, Mayhew views it as a reactionary move that ultimately reduces poetry to the status of a minor genre. The author then turns his attention to the poetry of José Angel Valente and Antonio Gamoneda, whose poetry embodies the continuation of modernism, and to the work of younger women poets of the last two decades of the twentieth century. Throughout this controversial and provocative book, Mayhew challenges received notions about the value of poetic language in relation to the larger culture and society. It turns out that the cultural ambition of modernist poetics is still highly relevant even in an age in which more cynical views of literature seem prevalent. Ultimately, Mayhew writes as an advocate for the survival of more challenging and ambitious modes of poetic writing in the postmodern age.